2014
DOI: 10.1039/c3gc41803k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free γ-valerolactone hydrogenation to 2-methyltetrahydrofuran catalysed by Ru/C: a reaction network analysis

Abstract: 2-Methyltetrahydrofuran (2-MTHF) is considered to be an attractive biomass based platform chemical with high potential as a biofuel compound and as a green solvent. 2-MTHF can be synthesised from bio-based levulinic acid (LA) and γ-valerolactone (GVL). Herein the optimum reaction conditions for the hydrogenation of GVL over Ru/C have been studied. A full conversion of GVL has been obtained under solvent free conditions with a maximum yield of 2-MTHF of 43%. The optimized conditions have been employed in a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 39 publications
9
144
1
1
Order By: Relevance
“…SiO 2 has the tendency to be converted into silica gel at all pH values, whereas Al 2 O 3 is well-known to convert into boehmite (AlO(OH)) at pH values between 4.5 and 11.5. TiO 2 , calculated to be stable over the entire pH range, and ZrO 2 are attractive alternatives [28], even though hydrated Zr(OH) 4 was found to be the thermodynamically most stable phase in water. Indeed, a screening study on LA hydrogenation involving 50 catalysts in a flow reactor system revealed that Pt on TiO 2 (P25 from Degussa) and ZrO 2 performed best, with constant GVL yields for runtimes exceeding 100 h (> 95 mol% at 200°C and 40 bar H 2, 11 wt.% LA in GVL) [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiO 2 has the tendency to be converted into silica gel at all pH values, whereas Al 2 O 3 is well-known to convert into boehmite (AlO(OH)) at pH values between 4.5 and 11.5. TiO 2 , calculated to be stable over the entire pH range, and ZrO 2 are attractive alternatives [28], even though hydrated Zr(OH) 4 was found to be the thermodynamically most stable phase in water. Indeed, a screening study on LA hydrogenation involving 50 catalysts in a flow reactor system revealed that Pt on TiO 2 (P25 from Degussa) and ZrO 2 performed best, with constant GVL yields for runtimes exceeding 100 h (> 95 mol% at 200°C and 40 bar H 2, 11 wt.% LA in GVL) [28].…”
Section: Introductionmentioning
confidence: 99%
“…The family of LA derivatives is large and some have much potential for commercialization. For instance, LA can be converted to 2-methyltetrahydrofuran (MTHF) and various levulinate esters, which may be used as gasoline and biodiesel additives, respectively [3][4][5][6][7][8]. δ-Aminolevulinic acid is a well-known herbicide and β-acetylacrylic acid has been proposed as a (co-)monomer for novel acrylate polymers [1].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The high energy density, lower flammablity, hydrophobic nature, low toxicity and high specific gravity of 2-MTHF make it suitable for use as fuel; thus 2-MTHF has been identified a nonpetroleum liquid fuel which can be substituted for or blended with gasoline. 2-MTHF has also been reported to be a better blend with gasoline than methanol and can be more easily integrated into the distribution stream of a refinery.…”
Section: Hydrogenation Of Levulinic Acid (La) To 2-methyltetrahydrofumentioning
confidence: 99%
“…[14] 2-MTHF is a green alternative to THF that favourable physical and chemical characteristics such as higher boiling point (80.2 o C), water immiscibility, reactivity and biodegredation pathways. [15][16][17][18][19] 2-MTHF can be used a component of P-series fuel, a non-petroleum liquid fuel which can be substituted for or blended with gasoline. [7,16] The transformation of LA to GVL and beyond typically involves a series of consecutive catalytic dehydration and reduction steps; although oxidative pathways are also possible.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Shaal et al [105] investigated the hydrogenation of GVL to 2-MTHF over Ru/C. The results indicated that GVL was fully converted, and a maximum 2-MTHF yield of 43% was achieved using no solvent.…”
Section: -Methyltetrahydrofuranmentioning
confidence: 99%